Stronger multilayer acrylic dielectric elastomer actuators with silicone gel coatings - Lau, Gih-Keong (2016)
Multilayer dielectric elastomer actuators (DEA) perform worst off than single-layer DEAs due to higher susceptibility to electro-thermal breakdown. This paper presents a hot-spot model to predict the electro-thermal breakdown field of DEAs and its dependence on thermal insulation. To inhibit the electrothermal breakdown, silicone gel coating was applied as barrier coating to multilayer acrylic DEA. The gel coating helps suppress the electro-thermally induced puncturing of DEA membrane at the hot spot. As a result, the gel-coated DEAs, in either a single layer or a multilayer stack, can produce 30% more isometric stress change as compared to those none-coated. These gel-coated acrylic DEAs show great potential to make stronger artificial muscles.